Do welfare-to-work initiatives work? Evidence from an activation programme targeted at social security recipients in Norway - Marit Rønsen; Torbjørn Skarðhamar (Statistics Norway, Research Department, 2007)
This paper presents results from an evaluation of a Norwegian initiative to combat poverty launched in 2003. Central to the plan is a broad spectrum of rehabilitation and activation measures intended to help long-term social security recipients from welfare to work. We illuminate short-term effects up to the end of 2004, taking a dual approach: First, we analyse transitions to work among participants in the programme and study the determinants of this process by means of survival analysis and multivariate hazard rate regression. Second, we address the question of programme effects adopting a quasi-experimental design based on propensity score matching. We find that the mean programme effect is positive, but only when work is defined fairly broadly. However, the impact varies by target group. For immigrants and single mothers, there is no impact whether we use a strict or less strict definition of work. For youth, the effect is even estimated to be negative, implying that they would have been better off without this initiative. The only significant effect in the desired direction is found among other long-term social security recipients, and applies for both the strict and less strict definition of employment. Moreover, this effect is fairly large.
Keywords: C41; H55; I38; J64; 330; Active labour market programmes; social security recipients; programme evaluation; propensity score matching.